Optimalisasi MP-ASI, Multivitamin, dan Produk Farmasi dalam Pencegahan Stunting di Sungai Kunyit Barat, Kabupaten Solok Selatan - Yahdian Rasyadi; Edi Suandi; Fitri Wahyuni; Eka Desnita; Elsa Marsellinda; Reza Hartamevia; Zakiatul Zahra; Indriana Fadilah; Selvi Merwanta (LPPM Universitas Pendidikan Mandalika (UNDIKMA), 2026)
This community service activity aims to strengthen family nutrition literacy regarding complementary feeding practices (MP-ASI), the utilization of local food resources, and the rational use of multivitamins and simple pharmaceutical products as part of stunting prevention efforts in Nagari Sungai Kunyit Barat, South Solok Regency. The program was implemented using a Participatory Action Research approach, involving 40 participants consisting of mothers of young children, community health volunteers (posyandu cadres), and local administrative stakeholders. Evaluation data were analyzed using descriptive qualitative techniques. The results indicate an improvement in participants’ knowledge and practical skills in age-appropriate complementary feeding, the utilization of animal-based protein sources (such as eggs and fish), and the rational use of multivitamins as supportive supplements rather than substitutes for main meals. Operationally, participants were able to design varied menus based on local food resources, and posyandu cadres demonstrated readiness to replicate the educational activities within the community. Overall, the activity demonstrates that community-based education integrating nutrition and community pharmacy literacy can effectively strengthen family capacity for stunting prevention.